A Estação arqueológica de Boucinhas, Regueira, Vitorino dos Piães, Ponte de Lima (Norte de Portugal) - Bettencourt, Ana M. S.; Dinis, António P.; Silva, Andreia; Veiga, André Mota; Ribeiro, Emanuel; Cardoso, Hugo; Boas, Luciano Vilas; Amorim, Maria João (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The article presents some of the results from the archaeological diggings, surveyed in July of 2003, in the archaeological site of Boucinhas, in the parish of Vitorino de Piães, municipality of Ponte de Lima. These studies were made in the interdisciplinary research project “The Entre-Douro-e-Minho landscape since middle of III to the end of II millenium BC”.